2019
DOI: 10.1002/oa.2748
|View full text |Cite
|
Sign up to set email alerts
|

Entheseal changes in ancient Egyptians from the pyramid builders of Giza—Old Kingdom

Abstract: Entheseal changes are distinct skeletal markings that occur where a muscle, tendon, or ligament inserts into bone cortex, in response to many factors including physical activity. Therefore, entheseal changes have been frequently used to reconstruct habitual life activities of ancient populations. The present study examines a sample of 195 ancient Egyptians from Giza—Old Kingdom (2700–2190 BC), the period of pyramid builders. The material consists of two burials that were identified as belonging to individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
1
7
0
2
Order By: Relevance
“…Several variables have been identified as possibly or probably influential factors that affect the frequencies of EC in archeological samples, including physical activities, mobility patterns, and body mass (e.g., Carballo‐Pérez et al, 2021; Godde et al, 2018; Laffranchi et al, 2020; Refai, 2019; Sparacello et al, 2020), but age at death remains the main factor explaining EC distribution in human skeletal samples. In our study, stages clearly correlate with age for both fibrocartilaginous and fibrous entheses.…”
Section: Discussionmentioning
confidence: 99%
“…Several variables have been identified as possibly or probably influential factors that affect the frequencies of EC in archeological samples, including physical activities, mobility patterns, and body mass (e.g., Carballo‐Pérez et al, 2021; Godde et al, 2018; Laffranchi et al, 2020; Refai, 2019; Sparacello et al, 2020), but age at death remains the main factor explaining EC distribution in human skeletal samples. In our study, stages clearly correlate with age for both fibrocartilaginous and fibrous entheses.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed a slightly higher use of the right‐side muscles, both in EC and CSG. This predominance is a known genetically determined phenomenon both in modern and archaeological populations (Refai, 2019; Ruff & Jones, 1981). However, the results in EC and CSG do not allow us to identify a pattern of unilateral activities since there were also high frequencies of enthesis related to activity of specific muscles of the left side.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, he performs active tasks more efficiently with the right muscles. The predominance of the right arm is a phenomenon of genetic influence studied in both modern and archaeological populations (Ruff & Jones, 1981;Refai, 2019;Carballo et al, 2021). It should be noted that laterality has been widely studied to understand better the gestural preference in specific activities of ancient populations (Al-Oumaoui et al, 2004).…”
Section: From Muscle To the Bone: An Osteoarchaeological Perspectivementioning
confidence: 99%